Analysis of Early Reading Ability of Children in Group B of Kindergarten Tut Wuri Handayani Samahani Aceh Besar - Riza Oktariana (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2021)
Reading is an activity of following a series of writings arranged in a linear manner. Experience is an important aspect of the reading process. Children who have a lot of experience will have a wider opportunity in developing an understanding of vocabulary in reading. The formulation of the problem in this study, what activities are done in training beginning reading skills in group B in TK Tut Wuri Handayani Samahani Aceh Besar. How is the description of beginning reading ability in group B in TK Tut Wuri Handayani Samahani Aceh Besar. What are the obstacles faced by teachers in teaching beginning reading skills to group B children in TK Tut Wuri Handayani Samahani Aceh Besar. The purpose of this study is to see a picture of the activities given to children in group B in TK Tut Wuri Handayani Samahani Aceh Besar. To see the beginning reading ability in group B children in TK Tut Wuri Handayani Samahani Aceh Besar. To find out the obstacles faced by teachers on the ability to read beginning in group B children in TK Tut Wuri Handayani Samahani Aceh Besar. The type of research is Qualitative research The instrument used is an interview, the sample size is 1 principal and 2 classroom teachers. The results show that beginning reading is very important for early childhood which will be the foundation of the beginning of reading. Teachers who teach at TK Tut Wuri Handayani Aceh Besar, are very understanding about the development of children's reading and also teachers at TK Tut Wuri Handayani Aceh Besar always encourage children by providing creative media that can attract children's attention in beginning reading so that teachers provide reading learning start by using a system of play while learning.